2021
DOI: 10.1186/s13073-021-00974-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides vulgatus and Bacteroides dorei predict immune-related adverse events in immune checkpoint blockade treatment of metastatic melanoma

Abstract: Background Immune checkpoint blockade (ICB) shows lasting benefits in advanced melanoma; however, not all patients respond to this treatment and many develop potentially life-threatening immune-related adverse events (irAEs). Identifying individuals who will develop irAEs is critical in order to improve the quality of care. Here, we prospectively demonstrate that the gut microbiome predicts irAEs in melanoma patients undergoing ICB. Methods Pre-, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 53 publications
(57 reference statements)
1
36
0
Order By: Relevance
“… 44 Its specific colonization was also identified as a low‐risk predictor of immune‐related adverse events in metastatic melanoma. 45 Previous works indicated that Alistipes spp. not only was reduced in COVID‐19 patients but also negatively correlated with COVID‐19 severity, 22 , 46 , 47 which may be contributed to its participation in tryptophan metabolism and protective role in intestinal immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Its specific colonization was also identified as a low‐risk predictor of immune‐related adverse events in metastatic melanoma. 45 Previous works indicated that Alistipes spp. not only was reduced in COVID‐19 patients but also negatively correlated with COVID‐19 severity, 22 , 46 , 47 which may be contributed to its participation in tryptophan metabolism and protective role in intestinal immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observe that B. dorei is enriched in ObMet while B. vulgatus is enriched in ObC ( Figure 2 and Supplementary Figure 3 ). This pattern, where the ratio of B. dorei to B. vulgatus differs with respect to treatment groups, was also observed in blockade treatments in metastatic melanoma ( Usyk et al, 2021 ) and with host epigenomic alterations of inflammatory bowel disease ( Ryan et al, 2020 ). It was proposed by Ryan et al (2020) , that this pattern may be indicative of colonic-crypt species-specific colonization and competition ( Sonnenburg et al, 2010 ; Lee et al, 2013 ) due to differences in metabolic capabilities ( Gutiérrez and Garrido, 2019 ).…”
Section: Discussionmentioning
confidence: 58%
“…Bacteroides vulgatus has been associated with the reduced risk of immune-related adverse events ( Usyk et al, 2021 ), including dermatological skin toxicity (where B. dorei anti-correlated) ( Zhang et al, 2021 ). Furthermore, B. vulgatus has been shown to be protective against Escherichia coli induced colitis of interleukin-2-deficient gnotobiotic mice ( Waidmann et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that DTX can effectively reverse the immunosuppressive TME by polarizing protumoral M2-phenotype TAMs to tumoricidal M1-phenotype TAMs [ 24 ]. Immunotherapy has received increasing attention due to its ability to activate host defenses to identify, attack, and eradicate cancer cells [ 70 , 71 ]. However, low immune response rate and individual differences undermine its antitumor efficacy.…”
Section: Resultsmentioning
confidence: 99%